PENGARUH KECEMASAN MATEMATIKA DAN PROKRASTINASI AKADEMIK SISWA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 7 BALIKPAPAN - Zuraidah Zuraidah; Tri Hariyati Nur Indah Sari; Suci Yuniarti (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2020)
The existence of students' negative views on mathematics causes anxiety and procrastination. This study aims to determine the effect of mathematical anxiety and academic procrastination on mathematics learning outcomes in class VIII SMP Negeri 7 Balikpapan. The research approach used is a quantitative approach with survey method. The population in this study were all eighth grade students of SMP Negeri 7 Balikpapan, as many as 362 students and a total sample of 72 students. The sampling technique uses cluster random sampling. Instruments used in this study was questionnaires and test. The data analysis technique used is multiple regression analysis with simultaneous test (F test) and partial test (t-test). The results obtained a significant value of 0,000 < 0,05, it could be concluded that there was a significant influence of mathematics anxiety and academic procrastination on mathematics learning outcomes of VIII grade students of SMP Negeri 7 Balikpapan. The results of the study showed that mathematics anxiety had a significant effect on mathematics learning outcomes with a significance value of 0,023 < 0,05. Then, academic procrastination has a significant effect on mathematics learning outcomes with a significance value of 0,012 < 0,05.